Critical Role of the Mesenteric Depot Versus Other Intra-abdominal Adipose Depots in the Development of Insulin Resistance in Young Rats - Catalano, Karyn J. (American Diabetes Association, 2010)
OBJECTIVE: Age-associated insulin resistance may be caused by increased visceral adiposity and older animals appear to be more susceptible to obesity-related resistance than young animals. However, it is unclear to what extent the portally drained mesenteric fat depot influences this susceptibility. RESEARCH DESIGN AND METHODS: Young high-fat–fed and old obese rats were subjected to 0, 2, 4, or 6 weeks of caloric restriction. Insulin sensitivity (S(I)) was assessed by hyperinsulinemic clamp and lean body mass (LBM) and total body fat were assessed by (18)O-water administration. RESULTS: Six weeks of caloric restriction caused a similar reduction in body weight in young and old animals (P = 0.748) that was not due to reduced subcutaneous fat or LBM, but rather preferential loss of abdominal fat (P < 0.05). Most notably, mesenteric fat was reduced equivalently in young and old rats after 6 weeks of caloric restriction (∼↓53%; P = 0.537). Despite similar visceral fat loss, S(I) improved less in old (↑32.76 ± 9.80%) than in young (↑82.91 ± 12.66%) rats versus week 0. In addition, there was significantly more reversal of fat accumulation in the liver in young (% reduction: 89 ± 2) versus old (64 ± 5) rats (P < 0.0001). Furthermore, in young rats, S(I) changed much more rapidly for a given change in mesenteric fat versus other abdominal depots (slope = 0.53 vs. ≤0.27 kg/min/mg per % fat). CONCLUSIONS: Improved S(I) during caloric restriction correlated with a preferential abdominal fat loss. This improvement was refractory in older animals, likely because of slower liberation of hepatic lipid. Furthermore, mesenteric fat was a better predictor of S(I) than other abdominal depots in young but not old rats. These results suggest a singular role for mesenteric fat to determine insulin resistance. This role may be related to delivery of lipid to liver, and associated accumulation of liver fat.